A comparative investigation on flank wear when turning three cast irons. (April 2018) - Tooptong, Sirisak; Park, Kyung-Hee; Kwon, Patrick
Abstract: A series of turning experiments is conducted on Flake Graphite Iron (FGI), Compacted Graphite Iron (CGI), and Nodular Graphite Iron (NGI) under dry condition. With uncoated carbide inserts, the adhesion layer, covering the entire tool-work interfaces, is formed when cutting CGI and NGI, which reduced flank wear compared to FGI. By contrast, the flank wear on the multilayer-coated inserts, obviously significantly reduced compared to the uncoated inserts, is significantly higher for CGI and NGI compared to FGI. Finite Element Analysis (FEA) is used to estimate the average flank temperature under various cutting conditions, which indicates the elevated cutting temperature with CGI and NGI. With the cutting temperatures from FEA simulations, the observed flank wear for FGI, CGI, and NGI conforms to the two-body abrasive wear model, indicating a common abrasive wear mechanism. Therefore, the main reason for the poor machinabilities of CGI and NGI is the higher cutting temperatures on the cutting tools when cutting CGI and NGI.